Handbook of research on entrepreneurship, innovation, and internationalization - Teixeira, Nuno Miguel, 1974-; Costa, Teresa Gomes da, 1964-; Lisboa, Ines Margarida, 1981- (Business Science Reference, 2019)
"This book examines the best practices for increasing a company's competitiveness through the study of three strategic factors in business success: entrepreneurship, innovation, and internationalization"--